Imaging function and relative light transmission of explanted opacified hydrophilic acrylic intraocular lenses - Naujokaitis, Tadas; Khoramnia, Ramin; Łabuz, Grzegorz; Choi, Chul Young; Auffarth, Gerd U.; Tandogan, Tamer (Diagnostics, 2023)
We evaluated the influence of intraocular lens (IOL) opacification on the optical performance of explanted hydrophilic acrylic IOLs. We performed a laboratory analysis of 32 Lentis LS-502-1 (Oculentis GmbH, Berlin, Germany) IOLs, explanted due to opacification, in comparison with six clear unused samples of the same IOL model. Using an optical bench setup, we obtained modulation transfer function (MTF), Strehl ratio, two-dimensional MTF, and United States Air Force (USAF) chart images. In addition, we assessed light transmission through the IOLs. The MTF values of opacified IOLs at 3-mm aperture were similar to those of clear lenses, with the median (interquartile range) values of 0.74 (0.01) vs. 0.76 (0.03) at the spatial frequency of 50 line pairs per millimeter in clear and opacified IOLs, respectively. The Strehl ratio of opacified lenses was not lower than that of clear lenses. The USAF-chart analysis showed a considerable reduction in brightness in opacified IOLs. The median (interquartile range) relative light transmission of opacified IOLs in comparison to clear lenses was 55.6% (20.8%) at the aperture size of 3 mm. In conclusion, the explanted opacified IOLs had comparable MTF values to those of clear lenses but significantly reduced light transmission.
Gesehen am 28.06.2023